IMPACT OF GIBBERELLIC ACID AND BORON TRIOXIDE NANOPARTICLES FOLIAR SPRAYING ON GROWTH, YIELD AND FRUIT QUALITY OF "ZAGHINIA" APRICOT TREES - A. M. I. Al-Janabi (مجلة الأنبار للعلوم الزراعية, 2024)
To determine the extent of growth response and yield of apricot trees cv. Zaghinia to foliar spraying with gibberellic acid at 0, 25, 50, and 75 mg L-1 and boron trioxide nanoparticles at 0, 10, and 20 mg L-1. A field trial was executed in a private orchard, in the governorate of Anbar, Iraq, during the growing season of 2023, in which trees were sprayed a week after full bloom, followed by two sprays at a three-week interval. A factorial experiment (4 x 3) on 36 trees, 7 years old was performed using a Randomized Complete Block Design (RCBD). With three replications and one tree for the experimental unit. Among all the treatments applied, (GA3 at 75 mg L-1 + Nano-boron at 20 mg L-1) treatment performed the highest annual shoot length (46.51 cm), chlorophyll content (41.04 mg 100 g-1 fresh weight), fruit set (53.86%), fruit retention (41.69%), fruit yield (14.43 kg tree-1), fruit weight (25.59 g), fruit volume (32.84 cm3), total soluble solids (15.12%) and carotene content (0.270 mg 100 g-1). While the treatment (GA3 at 25 mg L-1 + Nano-boron at 20 mg L-1) gave the highest shoot diameter (5.06 mm), and lowest acidity (0.81%). On the other hand, the control treatment recorded the lowest values, amounting to (26.61 cm, 4.91 mm, 34.11 mg 100 g-1 fresh weight, 39.27%, 30.19%, 8.56 kg tree-1, 17.92 g, 25.81 cm3, 13.53%, and 0.106 mg 100 g-1) for the traits length and diameter of annual shoots, chlorophyll content, fruit set and retention, total yield, fruit weight and volume, TSS, and carotene content respectively